I've never shared this with anybody: creole womens experience of racial and sexual discrimination and their Need for self recovery - Woods Downs, Socorro (Bilwi :URACCAN, 2002)
The experience of racial and sexual discrimination makes creole women good mothers and wives, rather than people with their own life inspirations.
Incluye Índice
Col. Tesis
Keywords: 1. AUTONOMY IN PRACTICE 2. EXPERIENCE OF RACIAL AND SEXUAL